Compound‐specific isotope analysis of benthic foraminifer amino acids suggests microhabitat variability in rocky‐shore environments. Issue 16 (24th July 2018) - Tsuchiya, Masashi; Chikaraishi, Yoshito; Nomaki, Hidetaka; Sasaki, Yoko; Tame, Akihiro; Uematsu, Katsuyuki; Ohkouchi, Naohiko
Abstract: The abundance and biomass of benthic foraminifera are high in intertidal rocky‐shore habitats. However, the availability of food to support their high biomass has been poorly studied in these habitats compared to those at seafloor covered by sediments. Previous field and laboratory observations have suggested that there is diversity in the food preferences and modes of life among rocky‐shore benthic foraminifera. In this study, we used the stable nitrogen isotopic composition of amino acids to estimate the trophic position, trophic niche, and feeding strategy of individual foraminifera species. We also characterized the configuration and structure of the endobiotic microalgae in foraminifera using transmission electron microscopy, and we identified the origin of endobionts based on nucleotide sequences. Our results demonstrated a large variation in the trophic positions of different foraminifera from the same habitat, a reflection of endobiotic features and the different modes of life and food preferences of the foraminifera. Foraminifera did not rely solely on exogenous food sources. Some species effectively used organic matter derived from endobionts in the cell cytoplasm. The high biomass and species density of benthic foraminifera found in intertidal rocky‐shore habitats are thus probably maintained by the use of multiple nitrogen resources and by microhabitat segregation among species as a consequence. Abstract : Diverse trophic ecology in microhabitat of coralline algae can be demonstrated by the compound‐specific stable nitrogen isotope analysis of amino acids and estimation of trophic position shown in this study. We confirmed a large variation in the trophic positions of different foraminifera from the same habitat, a reflection of endobiotic features and the different modes of life and food preferences of the foraminifera. The high biomass and species density of benthic foraminifera found in intertidal rocky‐shore habitats are thus probably maintained by the use of multiple nitrogen resources and by microhabitat segregation among species as a consequence.